A comparison of production of somatic embryo from three selected cocoa (Theobroma Cacao L.) clones - Norhashimah, Binti Abdul Razak (Universiti Malaysia Sarawak (UNIMAS), 2012)
Theobroma cacao L. is currently in the third ranking important commodity in Malaysia after oil palm and rubber. As to increase the best quality of cocoa production with faster propagation, the study of tissue culture for cocoa was carried out. The objectives of this study were to compare between two protocols for three selected cocoa clones, to discover the best protocol for better multiplication of cocoa propagation and to compare which cocoa clones give best response in somatic embryogenesis. This study is important in order to discover the best protocol to optimize the production of somatic embryos. The cocoa clones, KKM 1, MCB C5 and MCB C8 were studied in this experiment. Two protocols for somatic embryogenesis, Pennsylvania State protocol and Nestle protocol were compared in this study. The staminodes cultures were established based on Pennsylvania State and Nestle protocol for comparison of somatic embryogenesis. Based on the result, the clone for high propagation via somatic embryogenesis was cocoa clone MCB C8 (Nestle Protocol) under 10% Clorox® treatment with 82.7% of primary somatic embryos and 90 total explants producing secondary somatic embryos. Pennsylvania State Protocol was the best protocol to induce the somatic embryos for all selected cocoa clones.